Anotaciones generales sobre la historia empresarial de Valledupar (1950-1980): Una mirada desde el sector agropecuario (2019)
In the present article some annotations appear on the enterprise history of the municipality of Valledupar, as a result of the investigation carried on during the course of Masters in Management Sciences (2003-2005). In it, the obtained data of primary sources are conjugated such as notarial registries, articles of newspaper The Colombian and open interviews; and of secondary sources, consisting of the works by Eduardo Posada Carbó, Jaime Bonet Morón, Adolph Meisel Roca and Joaquin Viloria de la Hoz, among others, in addition to the writings about the cotton by Jorge Dangond Daza. The work became was carried on a contribution to the local historiography.